Microwave Irradiation Effect on the Dispersion and Thermal Stability of RGO Nanosheets within a Polystyrene Matrix - Alsharaeh, Edreese H. (Materials (Basel), 2014)
Polystyrene-reduced graphene oxide (PSTY/RGO) composites were prepared via the in situ bulk polymerization method using two different preparation techniques. The general approach is to use microwave irradiation (MWI) to enhance the exfoliation and the dispersion of RGO nanosheets within the PSTY matrix. In the first approach, a mixture of GO and styrene monomers (STY) were polymerized using a bulk polymerization method facilitated by microwave irradiation (MWI) to obtain R-(GO-PSTY) composites. In the second approach, a mixture of RGO and STY monomers were polymerized using a bulk polymerization method to obtain RGO-(PSTY) composites. The two composites were characterized by FTIR, (1) H-NMR, XRD, SEM, HRTEM, TGA and DSC. The results indicate that the composite obtained using the first approach, which involved MWI, had a better morphology and dispersion with enhanced thermal stability, compared with the composites prepared without MWI. Moreover, DSC results showed that the T(g) value of the composites after loading the RGO significantly increased by 24.6 °C compared to the neat polystyrene.